Teacher-Candidates' Perceptions of School Climate: A Mixed Methods Investigation - Lorenzo Cherubini (University of Windsor, 2008)
Preservice teacher-candidates are assigned to a number of different schools for their practicum experiences and as a result are immersed in a variety of school cultures and their respective climates. Interestingly, though matters related to school climate and the hidden curriculum are discussed in the literature, there is a lack of comprehensive research around preservice teachers' expectations and observations during their formal teacher education program. Given that beginning teachers' experiences are intensely impacted by their observations and experiences throughout their teacher training, the purpose of the study was to investigate teacher candidates' beliefs about the climate of schools at the beginning and near completion of their teacher education program. More specifically, this study employed a mixed methods research design to determine how beliefs about the hidden curriculum of schools compared to teacher candidates' impressions as they gained practice-teaching experience in various schools. The results may induce preservice education faculty to evaluate the underlying pedagogical causes that profoundly illuminate and engagingly implicate the tensions within teacher candidates' expectations of school climate and their observed realities.